2021
DOI: 10.3389/fnut.2021.690073
|View full text |Cite|
|
Sign up to set email alerts
|

How Early-Life Gut Microbiota Alteration Sets Trajectories for Health and Inflammatory Bowel Disease?

Abstract: Inflammatory bowel disease (IBD) is a recurrent chronic inflammatory condition of the intestine without any efficient therapeutic regimens. Gut microbiota, which plays an instrumental role in the development and maturation of the immune system, has been implicated in the pathogenesis of IBD. Emerging evidence has established that early-life events particularly maternal influences and antibiotic treatment are strongly correlated with the health or susceptibility to disease of an individual in later life. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Management of IBD has relied on anti-adhesion agents, anti-pro-inflammatory cytokine antibodies (e.g., anti-TNF antibody), and antibiotics. None of which could reverse the gut mucosa damages ( 2 ). Here, we first confirmed that DSS increased the expression of pro-inflammatory cytokines TNF-α ( Tnf ), Il1β , and Ifng , led to gut microbiota dysbiosis, and skewed immune responses in MLNs and the circulation, which in turn could increase intestinal permeability and bacterial translocation, consequently resulting in profound intestinal damage and colitis in young mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Management of IBD has relied on anti-adhesion agents, anti-pro-inflammatory cytokine antibodies (e.g., anti-TNF antibody), and antibiotics. None of which could reverse the gut mucosa damages ( 2 ). Here, we first confirmed that DSS increased the expression of pro-inflammatory cytokines TNF-α ( Tnf ), Il1β , and Ifng , led to gut microbiota dysbiosis, and skewed immune responses in MLNs and the circulation, which in turn could increase intestinal permeability and bacterial translocation, consequently resulting in profound intestinal damage and colitis in young mice.…”
Section: Discussionmentioning
confidence: 99%
“…Complex interactions between the gut microbiota, the epithelial barrier, and the host immune system determine intestinal homeostasis. A breakdown of regulatory pathways in any of these components may lead to chronic inflammatory conditions and inflammatory bowel disease (IBD) ( 1 , 2 ). Manifestating as Crohn’s disease and ulcerative colitis, IBD affects millions of people worldwide, and the incidence is increasing, especially in the newly industrialized areas, such as Asia ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also of interest is the role of the microbiome and how changes in gut microbiota early in life can impact windows of susceptibility and later-life disease. 1,14,15 Another mechanism that is gaining attention is environmentally induced somatic mosaicism. Exposures during critical windows of development can affect a person's normal tissue development but may also explain tissue-specific effects of hazards in the adult organism due to genetic mosaicism.…”
Section: Introductionmentioning
confidence: 99%